2015
DOI: 10.4103/2230-8210.159053
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between bone mineral density and oxidative stress in postmenopausal women

Abstract: Background:Postmenopausal osteoporosis affects large fraction of elderly women. Oxidative stress (OS) appears to be involved in its pathogenesis. The scarcity of human studies focusing on the correlation between bone mineral density (BMD) and OS in postmenopausal women has prompted us to study on this issue.Materials and Methods:We conducted a cross sectional study in 95 subjects, between 21–65 years of age, including postmenopausal osteoporotic females (n = 35), healthy postmenopausal females (n = 30) and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Studies have found that it is significantly elevated in the serum of women with OP after menopause (Ozgocmen et al 2007; Sendur et al 2009). The antioxidant enzymes SOD and GPX scavenge free radicals, and their levels have been found to be significantly lower in the serum of women with OP after menopause than in healthy postmenopausal women (Sharma et al 2015). If excessive free radical production exceeds the coping ability of the natural antioxidant defense mechanism, bone resorption may occur (Sheweita and Khoshhal 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that it is significantly elevated in the serum of women with OP after menopause (Ozgocmen et al 2007; Sendur et al 2009). The antioxidant enzymes SOD and GPX scavenge free radicals, and their levels have been found to be significantly lower in the serum of women with OP after menopause than in healthy postmenopausal women (Sharma et al 2015). If excessive free radical production exceeds the coping ability of the natural antioxidant defense mechanism, bone resorption may occur (Sheweita and Khoshhal 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and genetic studies of humans and rodents have indicated that ROS accumulation and increased oxidative stress play critical roles in the development of osteoporosis (Lee et al., 2015; Sharma et al., 2015). In bone tissues, excessive ROS production directly promotes osteoblast and bone-cell apoptosis (Sato et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of both dietary fat and CoQ 10 might be related to reactive oxygen species (ROS) roles on bone resorption. Several pieces of evidence link oxidative stress to BMD decrease in humans [ 43 , 44 ]. In addition, its association with age-dependent decline of bone mass and strength in sex steroid-sufficient female or male mice has been also reported [ 24 ].…”
Section: Discussionmentioning
confidence: 99%